2017
DOI: 10.1371/journal.pone.0188989
|View full text |Cite
|
Sign up to set email alerts
|

Substitutions of PrP N-terminal histidine residues modulate scrapie disease pathogenesis and incubation time in transgenic mice

Abstract: Prion diseases have been linked to impaired copper homeostasis and copper induced-oxidative damage to the brain. Divalent metal ions, such as Cu2+ and Zn2+, bind to cellular prion protein (PrPC) at octapeptide repeat (OR) and non-OR sites within the N-terminal half of the protein but information on the impact of such binding on conversion to the misfolded isoform often derives from studies using either OR and non-OR peptides or bacterially-expressed recombinant PrP. Here we created new transgenic mouse lines e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 78 publications
0
23
0
Order By: Relevance
“…Therefore, it is possible that residues 91–106 play an important role in the structural integrity of PrP C . Furthermore, the substitution of copper-binding histidine (H) residue to glycine (G) residue at position 95 in mouse PrP was reported to accelerate prion disease in mice after infection with RML prions [ 28 ], suggesting that copper-binding at H95 might also structurally stabilize PrP C and thereby play an inhibitory role in the conversion of PrP C into PrP Sc .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that residues 91–106 play an important role in the structural integrity of PrP C . Furthermore, the substitution of copper-binding histidine (H) residue to glycine (G) residue at position 95 in mouse PrP was reported to accelerate prion disease in mice after infection with RML prions [ 28 ], suggesting that copper-binding at H95 might also structurally stabilize PrP C and thereby play an inhibitory role in the conversion of PrP C into PrP Sc .…”
Section: Discussionmentioning
confidence: 99%
“…Given the known importance of the region from residues 90 to 231 for prion formation and the proximity of the non-OR region to the palindromic amyloidogenic motif, different studies have addressed the question whether Cu(II)-bound non-OR region has a role in prion generation and disease onset. A recent report showed that transgenic mice, TgPrP(H95G), with an amino acid replacement at residue H96 had shorter disease progression than WT control mice and classical clinical signs of TSE (51). We observed that alteration of Cu(II) coordination due to H96Y mutation causes spontaneous PrP Sc -like formation in neuronal cultured cells and accumulation in the acid compartments (21).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Tg(PrPΔOR)/ Prnp 0/0 mice remained susceptible to RML and 22L scrapie prions, developing the disease without elongated incubation times with slightly less PrP Sc ΔOR in their brains after infection with RML and 22L prions ( Table 2 ) [ 70 ], suggesting that the OR region might be involved in prion pathogenesis in a strain-dependent manner. However, Prnp 0/0 mice expressing PrP with histidine residues in the OR region replaced by glycine residues, termed PrP(TetraH>G), showed significantly prolonged incubation times after infection with RML prions ( Table 2 ) [ 76 ]. Further studies are needed to clarify whether or not the OR region might mediate strain-dependent prion pathogenesis.…”
Section: The N-terminal Domain Of Prp C In Priomentioning
confidence: 99%
“…Copper binding to recombinant mouse PrP was reported to cause novel intramolecular interactions, including those between the N-terminal residues 90–120 and the C-terminal residues 144–147 and its nearby residues 139–143, and between the N-terminal region comprising the OR region and the C-terminal residues 174–185 [ 92 ], suggesting that copper binding might also be involved in the unfolding of PrP C . Copper is able to bind to histidine residues located in the OR and post-OR regions [ 76 ]. We have shown that, while Tg(PrP∆OR)/ Prnp 0/0 mice were highly resistant to BSE prions, they still remained susceptible to RML and 22L prions [ 70 ], suggesting that copper binding to histidine residues in the OR region might be irrelevant to the unfolding of PrP C .…”
Section: The N-terminal Domain In Conversion Of Prp C mentioning
confidence: 99%